POLEMIK TERMINOLOGI KAJIAN ISLAM ANTARA ISLAMIC APOLOGETICS DAN ISLAMIC STUDIES PERSPEKTIF MAJID DANESHGAR - Farida Nur Afifah; Rini Susanti (EL-ADABI : Jurnal Studi Islam, 2024)
Islamic studies which are mostly carried out by Muslim academies, are apparently considered apologetic by Majid Daneshgar. According to Daneshgar, Islamic apologetics refer to a set of scholarly approaches and practices rooted in Muslim academies around the world that effectively protect Muslims from critical thinking about Islam and the koran. Through qualitative methods using literature study. This paper will analyze and criticize Daneshgar’s thinking using Jarl Manheim’s theory of the sociology of knowledge. The results of this research found two important points.  First, Daneshgar's thesis on the apologetics of Islamic studies in the Muslim academic environment cannot be separated from Majid Daneshgar's socio-historical construction.  How Daneshgar grew up in a Shiite tradition and was influenced by critical thoughts from Western scholars.  Second.  Daneshgar has overgeneralized Muslim academies.  Daneshgar only focuses on apologetic studies and ignores critical studies conducted by Muslim academies.  The most important finding from this research is that not all Western scholars' thoughts are suitable and should be adopted by Muslims.  The dominance of Western thought will make Muslims trapped in a captive mind so that Muslims lose their own originality.